The Impact of Climate Change on Food Insecurity in The Southern African Development Community - Mavodyo, Elisha (Universitas Airlangga, 2023)
Despite the fact that the Southern African region is one of the most vulnerable to climate change, research on the impact of climate change on food insecurity in the SADC region as a whole is scarce. We make two major contributions to the literature. First, we examine how climate change affects a group of SADC countries. Second, in contrast to previous studies, we supplement an analysis of climate change on crop yield with an analysis of climate change on other food insecurity indicators such as food affordability, malnutrition, and a food insecurity measure. Relying on the system generalized method of moments (GMM) estimator, results show that precipitation has a statistically significant impact on all four indicators of food insecurity in both its linear and non-linear forms; precipitation has the greatest impact on food affordability, followed by its negative impact on malnutrition; and temperature -whether in its linear or nonlinear form- has no statistically significant influence on all four indicators of food insecurity. However, temperature change gains statistical significance in explaining movements in food security after controlling for the interaction of temperature and precipitation. The policy implications of these findings highlight the need to increase precipitation availability in the SADC region by designing sustainable irrigation programs while also implementing climate change mitigation initiatives alongside those designed to ensure food affordability and access to a healthy and decent meal, particularly for the poor.